PENULISAN KREATIF DALAM NASKAH DRAMA “KABAYAN DI NEGERI ROMEO” KARANGAN ROSYID E. ABBY - Rista Trihandayani; Siti Gomo Attas; Gusti Yarmi (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2022)
This study analyzes the creative writing process for the creation of the play "Kabayan di Negeri Romeo" by Rosyid E. Abby which is an adaptation of the stories "Si Kabayan" and "Romeo and Juliet". The design in this study uses qualitative research, and the method taken in this study is a descriptive method. This study examines and describes the existence of creative writing in the drama script "Kabayan di Negeri Romeo". The drama script adapts the story by using the development of character, plot, and setting elements based on the stories "Si Kabayan" and "Romeo and Juliet". The results of this study will find the creative writing process of drama scripts which can later be used to write drama scripts.